Pengembangan Video Pembelajaran Matematika untuk Meningkatkan Hasil Belajar Siswa - Ade Kurniawan (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2023)
This study aims to develop an effective mathematics learning video to improve student learning outcomes in trigonometry material at SMA Negeri 1 Utan. The method used is Research and Development (R&D). In the analysis stage, the results of observations on students showed that 60% of students had low learning outcomes in trigonometry material. In the design stage, the developed learning video focused on the rules of sines and cosines. This video was designed with a structured storyboard and script to facilitate student understanding. The results of video validation by two lecturers of the Mathematics Education Study Program, Mandalika University of Education, showed that the video had good validity, with an average score of 3.69 (74%) from the first validator and 4.46 (89%) from the second validator. In the implementation stage, the video was tested on students of class X IPS 2, and the pre-test results showed an average score of 50, while the post-test after using the learning video showed an increase with an average score of 80. Evaluation of student and teacher responses showed positive results, with an average student response score of 4.2 (agree) and a teacher response score of 4.47 (strongly agree), indicating that the learning videos were effective in improving student learning outcomes. This study concluded that trigonometry-based mathematics learning videos can be used as an effective alternative in online learning to improve student learning outcomes, especially in materials considered difficult.